PEMANFAATAN LAYANAN SILANG LAYAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KLUNGKUNG - Yeni Suantari, Ni Putu; Haryanti, Ni Putu Premierita; Oka Sujana, A.A Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2021)
The purpose of this study was to determine the utilization inter library services at Dinas Kearsipan dan Perpustakaan Kabupaten Klungkung, the research method used qualitative descriptive and the research location at Dinas Kearsipan dan Perpustakaan Kabupaten Klungkung, Pojok Baca Petapan Park, and Perpustakaan Kelurahan Semarapura Kaja. The informant determination technique used purposive sampling technique with informants 6 (six) people. Data sources are primary and secondary data sources. The results of this study indicate that the utilization inter library services at Dinas Kearsipan dan Perpustakaan Kabupaten Klungkung is classified as good. This can be seen from the various collections provided so that they can add to existing library materials in libraries that receive inter library services and make it easier for users to meet their information needs and with inter library services to help users in using the library Keywords : Utilization. Inter Library Service, Public Library.